Targeting persistently activated inflammatory microenvironment to promote chronic wound healing - Dai, Yuxuan; Chen, Yu (Frontiers in Immunology, 2025)
The immune system plays a pivotal role in maintaining the balance of inflammatory responses and facilitating tissue repair and wound healing. However, under the combined influence of immune microenvironmental factors and external stimuli, immune cell dysfunction can lead to persistent activation of the inflammatory milieu, resulting in delayed or impaired wound healing. Therefore, regulating immune responses within the chronic inflammatory microenvironment and suppressing aberrant immune cell activation not only helps restore immune homeostasis but also effectively accelerates the wound healing process. Identifying and modulating novel targets associated with macrophage and T-cell dysregulation, as well as the crosstalk among immune cells, offers new insights and therapeutic strategies for the treatment of chronic inflammation-related disorders and wound repair. This review focuses on the molecular mechanisms underlying aberrant macrophage and T-cell activation, the intercellular crosstalk within the immune microenvironment, and their impact on the wound healing process. Furthermore, it highlights potential therapeutic targets for limiting persistent inflammation and re-establishing immune homeostasis. Elucidating these mechanisms and targets may provide promising avenues for the treatment of chronic inflammatory diseases and for advancing strategies in tissue repair and regeneration.